What are the Short-Term Outcomes in Multiple Sclerosis Patients after Total Knee Arthroplasty? - Newman, Jared M.; Sultan, Assem A.; Khlopas, Anton; Sodhi, Nipun; Faour, Mhamad; Piuzzi, Nicolas S.; Higuera, Carlos A.; Mont, Michael A. (The Journal of Knee Surgery, 2019)
Due to the paucity of evidence, this study was conducted to evaluate: (1) unique characteristics of multiple sclerosis (MS) patients and (2) short-term clinical outcomes, of primary total knee arthroplasty (TKA) in patients with MS (MS-TKA) compared with matched non-MS patients. MS patients who underwent TKA were identified using the Nationwide Inpatient Sample (NIS) database. The study sample consisted of 10,884 patients with MS and 56,45,227 control cohort. Various patient factors were compared. To control for potential confounders, with the use of propensity scores, MS-TKA patients were matched (1:3) to non-MS-TKA patients and regression analyses were performed to compare perioperative complications, length of stay (LOS), and discharge dispositions. Patients with MS were younger, more likely to be females, on corticosteroids, and more likely to have muscle spasms and gait abnormalities. Annual frequency of TKAs in MS patients increased from 1.16/1,000 TKAs in 2002 to 2.48/1,000 TKAs in 2013 (p < 0.001). Compared with the matched cohort, MS patients had significantly greater odds for any medical complication (odds ratio [OR] = 1.26; 95% confidence interval [CI], 1.11–1.44), longer mean LOS (mean difference: 0.15; 95% CI, 0.09–0.22), and had a greater chance of being discharged to a care facility (OR = 2.17; 95% CI, 1.96–2.40). In this study, we identified specific characteristics of patients with MS who had TKA and analyzed and compared their short-term TKA outcomes to non-MS patients. It was demonstrated that more patients with MS are undergoing TKA, and these patients were at a higher risk of perioperative complications, had longer LOS, and were more likely to be discharged to a sub-acute or inpatient facility. Orthopaedic surgeons should be cognizant of the increased risks and provide proper counseling to MS patients who are candidates for TKA.
Keywords: multiple sclerosis; total knee arthroplasty; complications; lengths of stay; charges